The COVID-19 Vulnerabilities and the Ubiquitous Artificial Intelligence Linkages - Bongs Lainjo (Emerging Trends in Disease and Health Research Vol. 8, 2022)
The aim of the study is to conduct an exploratory review of the Covid-19 pandemic by focusing on the theme of Covid-19 pandemic morbidity and mortality, considering the dynamics of artificial intelligence and quality of life (QOL). A review of the literature, anecdotal evidence, and reports on the morbidity of COVID-19, including the magnitude of its destructive consequences in nations such as the United States, Africa, the United Kingdom, China, and Brazil, among others, were used in this research work. The outcomes of this study revealed that the coronavirus’s destructive impacts are felt by a variety of vulnerable populations. The elderly, front-line workers, marginalised populations, visible minorities, and others are among them. The issue in Africa is particularly formidable due to a lack of infrastructure, as well as financial and human resources. Furthermore, scientists are effectively employing AI technology to improve the creation of vaccinations and pharmaceuticals. The pandemic also helped us recognise the necessity of inter-personal cooperation as well as shared ideals. The importance of healthcare workers and other frontline workers in reacting to the epidemic is also recognised. In addition, new techniques and effective health interventions have been found to be critical in treating the crisis’s negative impacts. This highlights the lessons that must be learned from the pandemic in order to deal with future waves of epidemics as efficiently as possible. One of these future implementations is ensuring the health and well-being of the elderly. Another crucial future implication is to make the best use of AI capabilities to combat the pandemic at all phases.